Determinant of production subcontracting in Nigeria (2000)
This paper analyzes the determinants of the volume of production subcontracting in Nigeria. The basic concepts are integration and industrial linkage, and production subcontracting. Data were collected from the sixty-eight contracting firms among 15 industrial estates/areas in the Lagos region. The volume of production subcontracting calculated in monetary terms was found to increase amongst the industry groups over the years. A one-way analysis of variance carried out for the volume of production subcontracting among the contracting firms was highly significant statistically. A stepwise multiple regression analysis, using the volume of production subcontracting as the dependent variable, and the size and structural characteristics of contracting firms as the independent variables was however, not statistically significant. It is argued that the nationality of the firm owner, whether local or foreign, may be significantly related to the volume of production subcontracting.